Opportunities and constraints for adoption of maize-legume mixed cropping systems in Laos. Issue 5 (2nd September 2020) - Lienhard, Pascal; Lestrelin, Guillaume; Phanthanivong, Ianlang; Kiewvongphachan, Xaisavanh; Leudphanane, Bounma; Lairez, Juliette; Quoc, Hoa Tran; Castella, Jean-Christophe
ABSTRACT: Land use and land cover have rapidly changed in Kham basin, northern Laos, with a rapid expansion of maize cultivated area. While maize monoculture has contributed to reduce rural poverty, many farmers are now confronted to declining yields, indebtedness, rising health and environmental concerns. Interventions at two different stages of the maize boom, i.e. expansion-intensification and distress-diversification phases, allowed capturing the main drivers of change in maize production systems, and assessing opportunities and constraints for the adoption of more sustainable maize-legume mixed systems. The successive innovations in maize cropping systems, i.e. introduction of hybrid seeds, motorized tillage, herbicides, service provision, planters, and mineral fertilizers, were mainly driven by productivity and profitability objectives. Farmers' interest in maize-legume mixed systems was low during maize expansion-intensification phase. The decline in maize profitability and new market outlets for legumes open new opportunity windows for maize-legume mixed systems. Yet, farmers' adoption of such systems is limited by (i) local perceptions of legumes as cash crops only, and (ii) farmers' least effort strategies that includes e.g. heavy herbicide use and livestock free roaming after maize harvest. Large-scale adoption of maize-legume mixed systems requires innovative intervention mechanisms to engage local stakeholders into redesigning their landscapes and value-chains.